'Goet, Origineel, ende Autentijcq’ - Jacqueline Hylkema (Early Modern Low Countries)
The question of whether printing privileges added more to publications than mere financial protection has often been raised in studies of printing privileges in the Dutch Republic. Traditionally, these discussions focus on the relationship between the authorities, printers, and privileged books, but what can the books that violated printing privileges tell us about the matter? This article offers a first exploration of the relationship between printing privileges, authority, and two different kinds of forgery (counterfeit and creative forgery) printed in the Dutch Republic in the seventeenth and early eighteenth century. The counterfeits of Jacob Cats’s Self-Stryt (1620) and the States Bible confirm that the authority of the States-General and the sense of official endorsement printing privileges added to a publication indeed played a role in the discourse of counterfeits in the Dutch Republic. But did this sense of endorsement make printing privileges an attractive tool in the publication of creative forgeries? It appears that the role of printing privileges was limited in this genre, but the possible reasons behind this are relevant too in the context of the relationship between authority and printing privileges.